Spaces of conservation of local breeds: the case of Yakutian cattle - Soini, Katriina; Ovaska, Ulla; Kantanen, Juha (Sociologia Ruralis, 2012)
The loss of farm animal genetic diversity became a major environmental issue during the course of the twentieth century. Numerous indigenous farm animal breeds have been replaced by commercial breeds alongside the modernisation of agriculture across the world. Indigenous farm animal breeds are mainly raised in marginal agricultural areas. Yakutian cattle are an indigenous Siberian cattle breed in the Russian Far East, which have a low output, but valuable characteristics that confer adaptation to the northern environment. This article identifies and analyses various spaces of conservation of the cattle, examines the power relationships within and between these spaces and discusses their implications for governance. The conservation of Yakutian cattle is embedded in the international agenda, which has been partly adopted by the Russian Federation. However, it is the Republic of Sakha and the Yakutian Institute of Agricultural Research that organise the conservation of Yakutian cattle de facto based on the law. The local communities in the Eveno-Bytantay district are responsible for practical conservation work in private households and the state [farm] enterprise. We suggest that although the cattle seem to be safeguarded, the current conservation policy does not support sustainable conservation in the long term. v 2012 ok